Closing the gap in travel medicine - Wilder-Smith, Annelies (Journal of travel medicine, 2017)
Why a theme issue on closing the gap? Which gap? There are many knowledge and practice gaps in travel medicine, with ever evolving new research priorities.1,2 H
Published: 30 March 2017
Gesehen am 18.06.2018